2021
DOI: 10.1038/s41598-021-83695-y
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic apparatus efficiency, phenolic acid profiling and pattern of chosen phytohormones in pseudometallophyte Alyssum montanum

Abstract: The present study investigated the response of non-metallicolous (NM) and metallicolous (M) Alyssum montanum shoots cultured in vitro on a medium supplemented simultaneously with heavy metals (HMs) to identify mechanisms involved in alleviating metal-induced damage. Plant status in respect to photosynthetic apparatus efficiency was determined and linked with changes in biochemical composition of shoots, namely phenolic acids’ and stress-related phytohormones. Results showed the considerable inter-ecotype diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…Although oxidative stress as a reaction to metals is one of the most studied issues recently [ 3 , 5 , 38 , 39 ], ROS transformation pathways, as a basis of adaptation to their excess amounts, have not been frequently compared between the representatives of different species sharing the same ecological niches or described for ecotypes of the same species representing different habitats. In this regard, our previous studies on serpentine and calamine ecotypes of Silene vulgaris (Caryophyllaceae) and the calamine ecotype of Alyssum montanum (Brassicaceae) have shown both species- and ecotype-dependent features [ 14 , 18 , 19 , 36 , 40 , 41 ]. The response of S. vulgaris to metallic elements was mainly related to the activity of antioxidant enzymes during in vitro cultivation on media enriched with Zn, Pb, and Cd at the same concentration as in the post-industrial habitat of the calamine ecotype [ 41 ].…”
Section: Functional Traits Of Plants Developed In Response To Severe ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Although oxidative stress as a reaction to metals is one of the most studied issues recently [ 3 , 5 , 38 , 39 ], ROS transformation pathways, as a basis of adaptation to their excess amounts, have not been frequently compared between the representatives of different species sharing the same ecological niches or described for ecotypes of the same species representing different habitats. In this regard, our previous studies on serpentine and calamine ecotypes of Silene vulgaris (Caryophyllaceae) and the calamine ecotype of Alyssum montanum (Brassicaceae) have shown both species- and ecotype-dependent features [ 14 , 18 , 19 , 36 , 40 , 41 ]. The response of S. vulgaris to metallic elements was mainly related to the activity of antioxidant enzymes during in vitro cultivation on media enriched with Zn, Pb, and Cd at the same concentration as in the post-industrial habitat of the calamine ecotype [ 41 ].…”
Section: Functional Traits Of Plants Developed In Response To Severe ...mentioning
confidence: 99%
“…The response of S. vulgaris to metallic elements was mainly related to the activity of antioxidant enzymes during in vitro cultivation on media enriched with Zn, Pb, and Cd at the same concentration as in the post-industrial habitat of the calamine ecotype [ 41 ]. In turn, the response of A. montanum was associated with the transformations of phenolic compounds, which, in the metallicolous ecotype, led to the synthesis of phenolic acids with a high ability to ROS scavenging and, in the non-metallicolous ecotype, to the synthesis of other compounds not involved in alleviating oxidative stress [ 19 ]. Interestingly, the common reaction of the metallicolous S. vulgaris and A. montanum individuals was the activity of GPX.…”
Section: Functional Traits Of Plants Developed In Response To Severe ...mentioning
confidence: 99%
See 1 more Smart Citation
“…ese two ecotypes were used in further in-depth research on the role of phenolic compounds and phytohormones in the defense mechanism against heavy metal ions that damage the photosynthetic apparatus (Muszyńska et al, 2021). For the M ecotype, these studies showed that jasmonic acid and flavonoids, which are involved in ROS scavenging, play an important role in the protection of photosystems, and the rearrangement of electron transport in thylakoid membranes.…”
Section: Plant Tolerance To Heavy Metal Ionsmentioning
confidence: 99%
“…Polyphenols, such as flavonols and anthocyanins, are generally recognized as molecules involved in stress protection in plants and have multiple functions in acclimation processes to an excessive amount of HMs [ 61 , 62 ]. It has been demonstrated in A. thaliana that anthocyanins play a major role in protecting against metal stresses [ 63 ].…”
Section: Arabidopsis Arenosa and Heavy Metalsmentioning
confidence: 99%